General Rehabilitation Principles for Patients with Cerebral Palsy After Single-Event Multilevel Surgery (SEMLS) - Olga A. Klochkova; Dmitry A. Popkov; Ayaz M. Mamedyarov; Ulvi F. Mamedov (Вопросы современной педиатрии, 2024)
Single-Event Multilevel Surgery (SEMLS) is the standard for surgical correction of secondary orthopedic deformities in cerebral palsy (CP). SEMLS include simultaneous correction of soft tissue contractures, bone deformities, incomplete and complete joint dislocation to improve the gait and functional activity of patients with CP. The surgery volume determines the need for planned and long-term postoperative rehabilitation, however, there are no confirmed guidelines, neither Russian, nor foreign, on the patient’s management during postoperative period. This review provides an analysis of rehabilitation approaches after SEMLS at CP, offers recommendations on preparation and step-by-step postoperative restoration of motor function, and prevention of any associated complications.